Alginate mediated functional aggregation of gold nanoclusters for systemic photothermal therapy and efficient renal clearance. (1st August 2020) - Zhao, Pin; Liu, Shuwei; Wang, Lu; Liu, Guojian; Cheng, Yanru; Lin, Min; Sui, Kunyan; Zhang, Hao
Highlights: Contributed from polysarchride ligand of sodium alginate, Au NCs are sensitive to aggregate in tumor microenvironment. The functional aggregation switches on photothermal conversion of AuNCs, endowing systemic photothermal therapy. Sodium alginate delays renal clearance of AuNCs in blood circulation and prolongs the half-life to ∼9.3 h. Abstract: For renal clearable nanoagents, it is challenging to delay the renal clearance to acquire efficient tumor accumulation. Herein, we report sodium alginate (SA) stabilized gold (Au) NCs. The Au NCs are of high biocompatibility and renal clearable. Contributed from the ligands of SA, the half-life (t1/2 ) of Au NCs is prolonged to ∼9.3 h, enhancing the tumor accumulation rate to 10.4 %ID/g. In tumor microenvironment (TME), the Au NCs are stimulated to functionally aggregate, which switches on the photothermal effect. Animal experiments prove that Au NCs aggregates are efficient photothermal therapy (PTT) agents for both local treatment of single tumors and systemic treatment of double-tumor models without causing noticeable side effects, confirming the biosecurity of Au NCs and systemic PTT. The switchable strategy of PTT may signify the establishment of a new systemic therapeutic methodology.